A camera trap survey in the community zone of Lobéké National Park (Cameroon) reveals a nearly intact mammalian community - (:unkn) unknown (My University, 2023)
Estimating the richness and abundance of animal species remains central to any conservation strategy of a given area. In remote and challenging environments such as tropical forests, camera traps have proven to be successful in documenting secretive wildlife communities compared to other survey methods, as they allow continuous monitoring without the presence of a human observer. Here, we used camera traps to characterise the community of medium and large terrestrial mammals in the community zone of Lobéké National Park, in southeastern Cameroon. We deployed a grid of 40 camera traps over a 5-week period, recording 5156 independent detection events over 1284 camera days. We recorded 35 species, many of them showing high detection rates compared to other sites in central Africa. These results highlight the little disturbance of the studied area within the park despite its accessibility to local communities. These results obtained from a standardised approach using an expanding technology offer valuable information about the wildlife community of Lobéké, and new insights for reconciling human activities with wildlife conservation.
Keywords: African Research